Curcumin derivative, 2,6-bis(2-fluorobenzylidene)cyclohexanone (MS65) inhibits interleukin-6 production through suppression of NF-κB and MAPK pathways in histamine-induced human keratinocytes cell (HaCaT) - Razali, Nurul Atika; Nazarudin, Nur Amiza; Lai, Kok Song; Abas, Faridah; Ahmad, Syahida (BioMed Central, 2018)
Background: Histamine is a well-known mediator involved in skin allergic responses through up-regulation of pro-inflammatory cytokines. Antihistamines remain the mainstay of allergy treatment, but they were found limited in efficacy and associated with several common side effects. Therefore, alternative therapeutic preferences are derived from natural products in an effort to provide safe yet reliable anti-inflammatory agents. Curcumin and their derivatives are among compounds of interest in natural product research due to numerous pharmacological benefits including anti-inflammatory activities. Here, we investigate the effects of chemically synthesized curcumin derivative, 2,6-bis (2-fluorobenzylidene)cyclohexanone (MS65), in reducing cytokine production in histamine-induced HaCaT cells. Methods: Interleukin (IL)-6 cytokine production in histamine-induced HaCaT cells were measured using enzyme-linked immunosorbent assay (ELISA) and cytotoxicity effects were determined using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay. Real-time polymerase chain reaction (RT-qPCR) was carried out to determine the inhibitory effects of MS65 on nuclear factor-kappa B (NF-κB) and mitogen activated protein kinase (MAPK) pathways. Results: Histamine enhanced IL-6 production in HaCaT cells, with the highest production of IL-6 at 97.41 ± 2.33 pg/mL after 24 h of exposure. MS65 demonstrated a promising anti-inflammatory activity by inhibiting IL-6 production with half maximal inhibitory concentration (IC50) value of 4.91 ± 2.50 μM and median lethal concentration (LC50) value of 28. 82 ± 7.56 μM. In gene expression level, we found that MS65 inhibits NF-κB and MAPK pathways through suppression of IKK/IκB/NFκB and c-Raf/MEK/ERK inflammatory cascades. Conclusion: Taken together, our results suggest that MS65 could be used as a lead compound on developing new medicinal agent for the treatment of allergic skin diseases.